Assessing quality parameters in dry-cured ham using microwave spectroscopy. (October 2015) - Bjarnadottir, S.G.; Lunde, K.; Alvseike, O.; Mason, A.; Al-Shamma'a, A.I.
Abstract: Microwave spectroscopy has been applied in numerous non-food industry applications, and recently also in the food industry, for non-destructive measurements. In this study, a dry-cured ham model was designed and chemical analyses were performed for determining water activity, water content and salt content (sodium chloride) for all samples. These chemical parameters were also measured using microwave spectroscopy, with a rectangular microwave cavity resonator. Results indicate that microwave spectroscopy may be a promising technique for determination of water activity, salt content and water content in dry-cured ham using either reflected or transmitted signals. Highlights: A high correlation was found between microwave measurements and aw in dry-cured ham. Water and salt contents also had a high correlation with microwave measurements. A promising technique for determination of aw, salt and water in dry-cured hams